Photocatalytic nitrogen fixation composite catalyst and preparation method thereof
By designing a multi-active center composite catalyst system and optimizing the preparation method, the problem of low nitrogen activation efficiency in photocatalytic nitrogen fixation technology is solved, and efficient nitrogen fixation effect is achieved and cost is reduced.
Patent Information
- Application Number
- CN202411691675.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
In photocatalytic nitrogen fixation technology, the inertness of nitrogen molecules and the high dissociation of N≡N bonds can make it difficult for nitrogen to be effectively activated and reduced on the surface of the photocatalyst, resulting in low efficiency.
A photocatalytic nitrogen-fixing composite catalyst is designed to reduce the hydrogen poisoning effect by calcining and autoclaving in different active centers by calcining and autoclaving treatment.
It effectively improves the efficiency of photocatalytic nitrogen fixation, reduces the cost of catalysts, and simplifies the batch preparation process.
Smart Images

Figure CN119500284A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of catalytic nitrogen fixation, and in particular to a photocatalytic nitrogen fixation composite catalyst and a preparation method thereof. Background Art
[0002] Photocatalytic nitrogen fixation is a technology that uses solar energy to convert nitrogen and water in the atmosphere into ammonia. It can be carried out at room temperature and pressure and is an ideal way to utilize energy. The challenge of photocatalytic nitrogen fixation technology lies in the inertness of nitrogen molecules and the high dissociation energy of N≡N bonds, which makes it difficult for nitrogen molecules to be effectively activated and reduced on the surface of photocatalysts.
[0003] In recent years, researchers have made some progress in the field of photocatalytic nitrogen fixation. For example, Professor Xiong Yujie's team at the University of Science and Technology of China introduced oxygen vacancies (Ovs) into TiO2, regulated the local electronic structure of oxygen vacancies, thereby controlling the hydrogenation path of N2 and improving the efficiency of photocatalytic nitrogen fixation. In addition, Professor Dong Fan's team designed a Pt cluster-modified titanium dioxide (Pt cluster / TiO2) catalyst, which achieved a coordinated redox reaction of methanol (CH3OH) and nitrogen (N2) to synthesize urea with high efficiency and selectivity.
[0004] Although some progress has been made, the efficiency of photocatalytic nitrogen fixation is still low, so it is difficult to achieve the ideal nitrogen fixation effect using ordinary semiconductors for photocatalytic nitrogen fixation. Summary of the invention
[0005] The embodiments of the present application provide a photocatalytic nitrogen fixation composite catalyst and a preparation method thereof, thereby improving the efficiency of photocatalytic nitrogen fixation.
[0006] In a first aspect, the present invention provides a method for preparing a photocatalytic nitrogen fixation composite catalyst, comprising:
[0007] The indium source compound is mixed with DMF (NN dimethylformamide) and TPA (terephthalic acid), dispersed in water, stirred for 20 minutes, stirred and refluxed at 120°C to 140°C, and centrifuged to obtain a first solid product, wherein the molar ratio of In:DMF:TPA is 2:1 to 3:2 to 3; the first solid product is washed and dried to obtain a second solid product; the second solid product is calcined at 300°C to 550°C for 2 hours under inert gas protection, and then naturally cooled to room temperature to obtain a third solid product; the third solid product is The three solid products are mixed with a copper source compound, an indium source compound, a sulfur source compound, a titanium source compound and water, dispersed into an ethanol solution, and stirred for 20 minutes to obtain a solid-liquid mixture, wherein the molar ratio of In:Cu:S:Ti:H2O is 3:1-3:2-3:1-3:1-6; the solid-liquid mixture is placed in a polytetrafluoroethylene-lined autoclave, maintained at 160°C-180°C for 12h-48h, naturally cooled and centrifuged to obtain a fourth solid product; the fourth intermediate product is washed to obtain the photocatalytic nitrogen fixation composite catalyst.
[0008] Furthermore, the indium source compound includes one or more of indium nitrate, indium sulfate, and indium chloride.
[0009] Furthermore, the copper source compound includes one or more of copper nitrate, copper sulfate, basic copper chloride, and copper citrate.
[0010] Furthermore, the sulfur source compound includes one or more of thioacetamide, ammonium sulfide, thiourea, and sodium thiosulfate.
[0011] Furthermore, the titanium source compound includes one or more of tetrabutyl titanate, tetraisopropyl titanate, and tetraethyl titanate.
[0012] Furthermore, the inert gas is argon.
[0013] Furthermore, the stirring rate of the stirring is 500-1000 rpm, and the centrifugal rate of the centrifugal treatment is 3500-8000 r / min.
[0014] Furthermore, the drying temperature is 80°C.
[0015] Furthermore, the washing includes washing with ethanol and water at least once each.
[0016] In a second aspect, an embodiment of the present application provides a photocatalytic nitrogen fixation composite catalyst, which is obtained by the preparation method of the first aspect.
[0017] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:
[0018] The embodiment of the present application adopts a multi-active center composite catalyst system so that the activation of nitrogen and hydrogen occurs at different active centers, and through the "activated hydrogen transfer" mechanism on the surface, the hydrogen poisoning effect on a single transition metal is effectively reduced, and the efficiency of photocatalytic nitrogen fixation is further improved. At the same time, the prepared catalyst has a low cost and the process is easy to prepare in batches. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0020] Figure 1 A flow chart of a method for preparing a photocatalytic nitrogen fixation composite catalyst provided in an embodiment of the present application;
[0021] Figure 2 An electron microscope image of the photocatalytic nitrogen fixation composite catalyst provided in the examples of the present application;
[0022] Figure 3 This is a comparison chart of the nitrogen fixation performance of the embodiments and comparative examples provided in this application. DETAILED DESCRIPTION
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0024] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0028] Photocatalytic nitrogen fixation is a technology that uses solar energy to convert nitrogen and water in the atmosphere into ammonia. It can be carried out at room temperature and pressure and is an ideal way to utilize energy. The challenge of photocatalytic nitrogen fixation technology lies in the inertness of nitrogen molecules and the high dissociation energy of N≡N bonds, which makes it difficult for nitrogen molecules to be effectively activated and reduced on the surface of photocatalysts.
[0029] In recent years, researchers have made some progress in the field of photocatalytic nitrogen fixation. For example, Professor Xiong Yujie's team at the University of Science and Technology of China introduced oxygen vacancies (Ovs) into titanium dioxide TiO2, regulated the local electronic structure of oxygen vacancies, thereby controlling the hydrogenation path of N2 and improving the efficiency of photocatalytic nitrogen fixation. In addition, Professor Dong Fan's team designed a Pt cluster-modified titanium dioxide (Pt cluster / TiO2) catalyst, which achieved a coordinated redox reaction of methanol (CH3OH) and nitrogen (N2) to synthesize urea with high efficiency and selectivity.
[0030] Although some progress has been made, the efficiency of photocatalytic nitrogen fixation is still low, and it is difficult to achieve the ideal nitrogen fixation effect.
[0031] Against this background, the present disclosure provides a method for preparing a photocatalytic nitrogen fixation composite catalyst, which can improve the efficiency of photocatalytic nitrogen fixation.
[0032] The preparation method of the photocatalytic nitrogen fixation composite catalyst is exemplarily described below with reference to the accompanying drawings.
[0033] Figure 1 : is a schematic diagram of a process for preparing a photocatalytic nitrogen fixation composite catalyst provided in an embodiment of the present application. Figure 1 This is only an execution order shown in the embodiment of the present application, and does not represent the only execution order of the preparation method of the photocatalytic nitrogen fixation composite catalyst. In the case where the final result can be achieved, Figure 1 The steps shown can be performed in parallel or in reverse. Figure 1 As shown, the preparation method may include:
[0034] S101, mixing the indium source compound with DMF and TPA, dispersing the mixture into water, stirring for 20 minutes, stirring and refluxing at 120° C. to 140° C. for 0.5 h to 2 h, and obtaining a first solid product by centrifugation.
[0035] Among them, the molar ratio of In:DMF:TPA=2:1~3:2~3.
[0036] S102, washing the first solid product and drying it to obtain a second solid product.
[0037] S103, calcining the second solid product at 300° C. to 550° C. for 2 h under the protection of an inert gas, and then naturally cooling to room temperature to obtain a third solid product.
[0038] It should be noted that the third intermediate product is tubular indium oxide.
[0039] S104, mixing the third solid product with a copper source compound, an indium source compound, a sulfur source compound, a titanium source compound and water, dispersing the mixture into an ethanol solution, and stirring for 20 minutes to obtain a solid-liquid mixture.
[0040] Among them, the molar ratio of In:Cu:S:Ti:H2O=3:1~3:2~3:1~3:1~6.
[0041] It should be noted that there is no restriction on the order of mixing the third solid product, copper source compound, indium source compound, sulfur source compound, titanium source compound, water, and ethanol solution. There is no need to deliberately follow the mixing order in S104 of this embodiment, as long as the molar ratio In:Cu:S:Ti:H2O=3:1~3:2~3:1~3:1~6.
[0042] S105, placing the solid-liquid mixture into a polytetrafluoroethylene-lined autoclave, maintaining it at 160° C. to 180° C. for 12 h to 48 h, cooling it naturally, and then centrifuging it to obtain a fourth solid product.
[0043] S106. Wash the fourth intermediate product to obtain a photocatalytic nitrogen fixation composite catalyst.
[0044] It should be noted that the chemical formula of the photocatalytic nitrogen fixation composite catalyst can be C-In2O3-CuInS2@TiO2, and its Chinese name is carbon-indium oxide-indium sulfur copper supported titanium dioxide composite catalyst.
[0045] In some possible implementations, the indium source compound includes one or more of indium nitrate, indium sulfate, and indium chloride.
[0046] In some possible implementations, the copper source compound includes one or more of copper nitrate, copper sulfate, basic copper chloride, and copper citrate.
[0047] In some possible embodiments, the sulfur source compound includes one or more of thioacetamide, ammonium sulfide, thiourea, and sodium thiosulfate.
[0048] In some possible implementations, the titanium source compound includes one or more of tetrabutyl titanate, tetraisopropyl titanate, and tetraethyl titanate.
[0049] In some possible implementations, the inert gas is argon.
[0050] In some possible implementations, the stirring rate of the stirring is 500-1000 rpm, and the centrifugal rate of the centrifugal treatment is 3500-8000 r / min.
[0051] In some possible implementations, the drying temperature is 60°C to 100°C, preferably 80°C.
[0052] In some possible embodiments, washing comprises washing with ethanol and water at least once each, preferably three times.
[0053] Figure 2 This is an electron microscope image of the photocatalytic nitrogen fixation composite catalyst provided in the embodiment of the present application. Through the preparation method of this embodiment, the following can be obtained: Figure 2 The photocatalytic nitrogen fixation composite catalyst is shown.
[0054] The preparation method of this embodiment can increase the catalyst crystal defects through the compounding of materials, thereby effectively exposing the active sites. By designing a composite catalyst system, the activation of nitrogen and hydrogen occurs at different active centers, and the rod-shaped hollow pore structure further improves the efficiency of photocatalytic nitrogen fixation. Through the "activated hydrogen transfer" mechanism on the surface, the hydrogen poisoning effect on a single transition metal is effectively reduced, further improving the efficiency of photocatalytic nitrogen fixation. In addition, the construction of a heterojunction after compounding also improves the efficiency of nitrogen fixation. Compared with metal oxides, the band gap of metal sulfides is narrower than that of oxides, which is more conducive to the absorption of visible light.
[0055] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0056] It can be understood that all raw materials used in the embodiments of the present invention can be purchased commercially.
[0057] Example 1
[0058] Disperse and dissolve 0.1 mol of indium nitrate, 0.1 mol of DMF and 0.1 mol of TPA in 30 ml of water, stir at a stirring rate of 500-1000 rpm for 20 min, stir and reflux at 135°C for 2 h, centrifuge, wash with ethanol and water 3 times each, and dry at 80°C to powder. The obtained powder is calcined at 550°C for 2 h under argon protection, and naturally cooled to room temperature to obtain tubular C-In2O3.
[0059] Take 0.2g of the prepared tubular C-In2O3 and add it to 30ml of ethanol solution containing 0.3g of indium nitrate, 0.1g of basic copper chloride, 0.07g of thioacetamide, 0.3g of tetrabutyl titanate, and 0.02g of water. After stirring at a stirring rate of 500-1000rpm for 20 minutes, the mixture is transferred to a 50mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 160°C for 12 hours. After natural cooling, the product is centrifuged and washed with ethanol and H2O three times each to obtain a C-In2O3-CuInS2@TiO2 composite catalyst (i.e., the above-mentioned photocatalytic nitrogen fixation composite catalyst).
[0060] Example 2
[0061] Disperse and dissolve 0.1 mol of indium nitrate, 0.05 mol of DMF and 0.1 mol of TPA in 30 ml of water, stir at a stirring rate of 500-1000 rpm for 20 min, stir and reflux at 120°C for 2 h, centrifuge the product and wash it with ethanol and water three times each, and dry it at 80°C to powder. The obtained powder is calcined at 330°C for 2 h under argon protection and cooled naturally to room temperature to obtain tubular C-In2O3.
[0062] Take 0.2g of the prepared tubular C-In2O3 and add it to 30ml of ethanol solution containing 0.3g of indium nitrate, 0.035g of basic copper chloride, 0.050g of thioacetamide, 0.113g of tetrabutyl titanate, and 0.006g of water. After stirring at a stirring rate of 500-1000rpm for 20 minutes, the mixture is transferred to a 50mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 160℃ for 24 hours. After natural cooling, the product is centrifuged and washed with ethanol and H2O three times each to obtain a C-In2O3-CuInS2@TiO2 composite catalyst.
[0063] Example 3
[0064] Disperse and dissolve 0.1 mol of indium nitrate, 0.15 mol of DMF and 0.15 mol of TPA in 30 ml of water, stir at a stirring rate of 500-1000 rpm for 20 min, stir and reflux at 140°C for 2 h, centrifuge the product and wash it with ethanol and water three times each, and dry it at 80°C to powder. The obtained powder is calcined at 550°C for 2 h under argon protection and cooled naturally to room temperature to obtain tubular C-In2O3.
[0065] Take 0.2g of the prepared tubular C-In2O3 and add it to 30ml of ethanol solution containing 0.3g of indium nitrate, 0.11g of basic copper chloride, 0.075g of thioacetamide, 0.339g of tetrabutyl titanate, and 0.036g of water. After stirring at a stirring rate of 500-1000rpm for 20 minutes, the mixture is transferred to a 50mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 180℃ for 48 hours. After natural cooling, the product is centrifuged and washed with ethanol and H2O three times each to obtain a C-In2O3-CuInS2@TiO2 composite catalyst.
[0066] Comparative Example 1
[0067] In2O3 obtained by general preparation method.
[0068] Comparative Example 2
[0069] CuInS2 obtained by general preparation method.
[0070] Effect verification
[0071] The C-In2O3-CuInS2@TiO2 composite catalysts prepared by Examples 1-5, the In2O3 prepared by Comparative Example 1, and the CuInS2 prepared by Comparative Example 2 were tested for photocatalytic nitrogen fixation performance. The obtained nitrogen fixation performance is as follows: Figure 3 shown. Figure 3 This is a comparison chart of the nitrogen fixation performance of the embodiments and comparative examples provided in this application.
[0072] refer to Figure 3 It can be seen that all the embodiments and comparative examples cannot achieve nitrogen fixation in a dark environment. In a light environment, the nitrogen fixation performance of Embodiment 1 and Embodiment 2 is much higher than that of Embodiment 3 and Comparative Example 2, and the nitrogen fixation performance of Embodiment 3 is also higher than that of Comparative Example 2. Comparative Example 1 cannot achieve nitrogen fixation in a light environment.
[0073] Although the present application provides method operation steps as described in the embodiments or flow charts, more or fewer operation steps may be included based on conventional or non-creative work. The order of steps listed in this embodiment is only one way of executing the steps among many, and does not represent the only execution order.
[0074] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A method for preparing a photocatalytic nitrogen fixation composite catalyst, characterized in that: include: The indium source compound is mixed with DMF and TPA, dispersed in water, stirred for 20 minutes, stirred and refluxed at 120° C. to 140° C., and centrifuged to obtain a first solid product, wherein the molar ratio of In:DMF:TPA is 2:1 to 3:2 to 3; The first solid product is washed and then dried to obtain a second solid product; The second solid product is calcined at 300° C. to 550° C. for 2 h under inert gas protection, and then naturally cooled to room temperature to obtain a third solid product; The third solid product is mixed with a copper source compound, an indium source compound, a sulfur source compound, a titanium source compound, and water, dispersed into an ethanol solution, and stirred for 20 minutes to obtain a solid-liquid mixture, wherein the molar ratio of In:Cu:S:Ti:H2O is 3:1-3:2-3:1-3:1-6; The solid-liquid mixture is placed in a polytetrafluoroethylene-lined autoclave, maintained at 160° C. to 180° C. for 12 h to 48 h, cooled naturally, and then centrifuged to obtain a fourth solid product; After washing the fourth intermediate product, the photocatalytic nitrogen-fixing composite catalyst is obtained.
2. The preparation method according to claim 1, characterized in that: The indium source compound includes one or more of indium nitrate, indium sulfate, and indium chloride.
3. The preparation method according to claim 1, characterized in that: The copper source compound includes one or more of copper nitrate, copper sulfate, basic copper chloride, and copper citrate.
4. The preparation method according to claim 1, characterized in that: The sulfur source compound includes one or more of thioacetamide, ammonium sulfide, thiourea, and sodium thiosulfate.
5. The preparation method according to claim 1, characterized in that: The titanium source compound includes one or more of tetrabutyl titanate, tetraisopropyl titanate, and tetraethyl titanate.
6. The preparation method according to claim 1, characterized in that: The inert gas is argon.
7. The preparation method according to claim 1, characterized in that: The stirring rate of the stirring is 500-1000 rpm, and the centrifugal rate of the centrifugal treatment is 3500-8000 r / min.
8. The preparation method according to claim 1, characterized in that: The drying temperature is 80°C.
9. The preparation method according to claim 1, characterized in that: The washing comprises washing with ethanol and water at least once each.
10. A photocatalytic nitrogen fixation composite catalyst, characterized in that: The composite catalyst is obtained by the preparation method according to any one of claims 1 to 9.